Está en la página 1de 4

(x 2 +

dy

4) dx = xy

x sen ydx + (x 2 + 1) cos ydy = 0 y(1) = π/2

T (t) t T T 0

dT

dt

= k(T 0 T ) K > 0

300 200 71 70

239 24360

(x 2 y 2 )dx + 3xydy = 0

xy y = x tg

y

x

(cos xx sen x+y 2 )dx+2xydy = 0 y = 1 x = π

2 + x dx x 2 + y dy = 0

x

y

y 3

(y 2 x)dx + 2ydy = 0

(x 2 + y 2 + x)dx + xydy = 0

xy 2y = x 2

90 10 50

y + xy = xe x 2 y 3

y + 6y + 12y = 0

y 4y = 0

y + 4y + 4y = 0 y(0) = 2, y (0) = 1

s F r s F r (s) = ks k m w = mg F r = ks mg = ks

t x(t) F = ma = mx (t)

mx = k(s + x) + mg = ks + mg kx = kx

muelle sin peso

s

en sistema equilibrio masa-resorte
sistema masa-resorte
x
< 0
F r = ks
F r = k(s + x)
x
= 0
m
x
> 0
mg
x(t)

mg

s

x

k

mx = kx x + m x = 0 x + ω 2 x = 0 ω 2 =

k

m

x (t)

mx = kx βx ,

β > 0

β

k

x + m x + m x = 0

t

x (t) β = 10

(1)

(1)

y 2y 3y = 2 sen x

y 2y = x + 2e x

y 2y + y = e x

2x x > 0

y y = e 2x sen(e x )

f (t)

β

mx = kx βx + f(t) x + m x +

k

m

x = f(t)

m

β = 0

x + k

x = f(t)

m

m

f (t) = sen( 195t) t